PARTISIPASI POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH KABUPATEN PELALAWAN DI KECAMATAN UKUI TAHUN 2015 - Puti Nilam Suri; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The title of this research is the Participation of Political Society in the Election of Head of Pelalawan Regency in Ukui Sub-district 2015. Based on the background The implementation of democracy in Indonesia is growing, one of which is realized in the implementation of regional head election. The existence of the election of regional heads of each individual or community group can manifest their will voluntarily, without influence from anyone. In this case every member of the community can directly vote in the election and be active in attending his political activities. But the liveliness of community members both in voting and campaign activities must be driven by an attitude of orientation that is so high. Besides that, awareness and motivation of citizens in political activity is very important to sustain the political participation level on the election of regional head. Due to the enthusiastic attitude of citizens in political participation it certainly leads to the consequences on a stable political order. So is the case in Kecamatan Ukui Pelalawan District where the low level of public participation against the election of Head of Region in 2015.The type used in this study is quantitative with Comparative Causal Studies. Data collection techniques used in this study are, questionnaires (questionnaires), interviews and documentation. The location of the research was conducted in Kecamatan Ukui. Based on the results of analysis conducted on research data to reveal and answer research questions relating to community participation in Pelalawan District elections in Kecuk ukui can be concluded that the participation of people in Ukui Sub-district is very low in comparison with other districts this is caused by several factors Namely socialization, social economy, political belief and political awareness.Keywords: Community participation, Election of Head of Region